Using Public Deliberation to Set Priorities: The Case of COVID-19 Vaccine Access in New York City. Issue 1 (January 2022) - Scherer, Maya; Kamler, Alexandra; Weiss, Linda; Blacksher, Erika; Jeavons, Jessica; Gold, Marthe R.
Abstract : Context: The COVID-19 pandemic has resulted in a record number of deaths in the United States and tremendous economic and personal strain. During 2020, in anticipation of a vaccine to slow the spread of disease, local and state governments in the United States developed plans for vaccine prioritization, given a limited initial supply. Recognizing the challenges inherent in prioritization, the New York City (NYC) health department sought guidance from members of the public about the fairest approach to early-stage vaccine distribution. Objective: To solicit recommendations from NYC residents on priorities regarding vaccine access for essential worker occupations, considering risk factors and preferred approaches to fairness. Implementation: Five public deliberations were conducted with NYC residents (N = 91). Participants heard presentations on the COVID-19 vaccine, the local distribution of illness and death, and approaches to fairness in the context of deliberating on priorities for 6 essential worker occupations and 4 risk factors. Discussions were transcribed, and transcriptions were coded and analyzed using preidentified and emergent themes. Pre- and post-surveys, focused on factors relevant to prioritization, were administered during each public deliberation. Results: Recommendations for prioritization emphasized risk of severe morbidity and mortality, and work and neighborhood conditions with fewer protections (eg, in-person work, exposure to many people). Participants prioritized elementary schoolteachers, grocery store workers, and bus drivers, underlying health conditions, and neighborhood of residence. Participants focused on equity, recognizing that those at highest risk were largely low-income populations of color and individuals living in low-resourced neighborhoods. Conclusions: Participants' focus on equity, and acknowledgment of racial and ethnic disparities, revealed a nuanced understanding of the broader determinants of health. Recommendations reinforced the NYC health department's approach to vaccine distribution. Public Health Implications: Results from these public deliberations confirmed community support for approaches prioritizing health equity, recognizing both societal and personal factors affecting vulnerability to poor health.